Nongenomic cardiovascular effects of triiodothyronine in euthyroid male volunteers - Schmidt, Bernhard; Martin, Nicole; Georgens, Anette Christiane; Tillmann, Hanns-Christian; Feuring, Martin; Christ, Michael; Wehling, Martin (The journal of clinical endocrinology & metabolism, 2002)
T3 has been shown to exert cardiovascular effects. These effects have not yet been defined with regard to the mode of action (nongenomic vs. genomic) and with regard to an interaction with the adrenergic system in humans. To address these issues we conducted a randomized, double blind, 6-fold cross-over trial in 18 healthy male volunteers. After pretreatment with the β-agonist dobutamine, the β-blocking agent esmolol, or placebo (0.9% NaCl), 100 μg T3 or placebo were injected. Primary target variables were systemic vascular resistance (SVR) and cardiac output (CO) within 45 min after injection of T3vs. placebo after placebo pretreatment. Sympatho-vagal balance was assessed by measurement of heart rate variability.T3 caused a lower SVR and a higher CO than placebo (P < 0.001) after pretreatment with placebo. An increased low frequency (LF)/high frequency (HF) ratio (power in LF/power in HF band) after T3 compared with placebo (P = 0.004) suggests an increase in sympathetic tone. After pretreatment with dobutamine, the effects of T3 on SVR and CO were abolished, and the effect on LF/HF ratio was reversed. After pretreatment with esmolol, the effects on SVR and LF/HF ratio were reversed. Our data show, for the first time, nongenomic cardiovascular effects of T3 in humans.